Translanguaging Practices in VSTEP Preparation Courses: Pedagogical Implications for Vietnamese EFL Contexts - Minh Toan, Pham (Journal of Studies in the English Language, 2025)
This mixed-methods study investigated teacher-reported translanguaging practices in Northern Vietnamese VSTEP preparation courses. Building on previous Vietnamese research documenting strategic L1 use in EFL contexts, this study extended investigation to assessment-oriented environments. Data were collected from 164 VSTEP preparation teachers through questionnaires and interviews with 12 participants. Teachers reported employing translanguaging selectively, with highest frequency for assessment-focused functions—explaining task instructions and clarifying evaluation criteria. Significant variations emerged across skill areas: writing preparation showed highest reported frequency (M = 3.68, SD = 0.76), speaking the lowest (M = 2.63, SD = 0.89). Principal component analysis identified three dimensions based on theoretical expectations that teachers employ translanguaging for distinct functions: assessment-focused (32.1% of variance), content-focused, and affective-focused. Teaching experience significantly influenced reported frequency, with less experienced teachers employing more frequent translanguaging. Teachers also reported observing strategic student translanguaging patterns for metacognitive purposes such as analyzing mistakes and discussing test-taking strategies. The research extends translanguaging theory to assessment-oriented contexts while challenging monolingual ideologies underpinning standardized testing. For Northern Vietnamese EFL education, findings provide teacher perception data for understanding policy-practice tensions, though implications remain tentative given the absence of learning outcome measurements.